Synthesis of FeâLiâCr Multinuclear Complexes as Molecular Magnet Materials - Djulia Onggo; Iis Siti Jahro; Fahimah Martak; Ismunandar Ismu (Institute for Research and Community Services (LPPM) ITB, 2008)
Multinuclear complexes have received considerable interest as molecular magnet materials. Up to now, several complex compounds based on bidentate ligand 2,2' bipyridine have been synthesized. In this research, the Fe-Li-Cr multinuclear complexes with derivative 2'2- bipyridine ligands: 2-(2'-pyridyl)quinoline(pq), 2,2'-Pyridil(pdl) have been synthesized. The oxalate (ox) ligand has also been used as a bridging ligand in these multinuclear complexes. The chemical formula of Li[FeCr(ox)2(pq)(BF4)2(H2O)2] and [Fe(pdl)n][LiCr(ox)3] complexes have been verified using metal and C, H, N elemental analysis data. The IR spectra in 350